2004
DOI: 10.1093/annonc/mdh426
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of PET imaging to the initial staging and prognosis of patients with Hodgkin's disease

Abstract: PET scanning is an interesting new modality for the accurate staging of patients with HD and frequently shows a higher stage than conventional methods. PET should be performed at initial diagnosis and should be included in prospective studies of patients with HD. Upstaging by PET may represent a risk factor for a more advanced stage or a biologically more aggressive tumor. Patients with early-stage disease as identified by conventional methods have a significant risk of treatment failure if a more advanced sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…Our results are in keeping with earlier reports 11,[13][14][15][16] that PET stages HL patients differently to ceCT in ;15% to 30% of cases. Early reports had fewer patients, were retrospective, and were published prior to the widespread introduction of PET-CT. [11][12][13][14][15][16] More recently, Hutchings et al 3 compared PET with CT staging prospectively in 99 patients with HL (61 with PET-CT), and Rigacci et al 10 in 186 patients (56 with PET-CT).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in keeping with earlier reports 11,[13][14][15][16] that PET stages HL patients differently to ceCT in ;15% to 30% of cases. Early reports had fewer patients, were retrospective, and were published prior to the widespread introduction of PET-CT. [11][12][13][14][15][16] More recently, Hutchings et al 3 compared PET with CT staging prospectively in 99 patients with HL (61 with PET-CT), and Rigacci et al 10 in 186 patients (56 with PET-CT).…”
Section: Discussionsupporting
confidence: 93%
“…[11][12][13][14][15][16] Previous publications compared imaging techniques but do not report the impact of imaging on the more relevant final clinical stage, inclusive of bone marrow biopsy, and some publications included patients with HL and non-Hodgkin lymphoma (NHL). [17][18][19][20][21] Response assessment with the 5-PS has been reported by a number of investigators to have good interobserver agreement in a training set of 50 patients, 22 in a study of 260 advanced HL patients with international expert readers, 23 and in pediatric HL.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an early FDG-PET assessment of response to chemotherapy is becoming a routine part of management in HL and histologically aggressive NHL. Although the total number of reported NL cases diagnosed by FDG-PET/CT is still small, positive findings are highly suggestive of a diagnosis of NL, particularly in patients with a known history of hematologic malignancy [1,6]. Furthermore, FDG-PET/CT can often diagnose NL when other diagnostic modalities have failed [7], and can allow disease extent to be visualized and therapeutic response to be determined [8].…”
Section: Case Reportmentioning
confidence: 99%
“…The use of PET in initial staging of HD up-staged 28.8% of the patients as compared to other imaging modalities and only 2.7% of the patients were down-staged. 12 The results indicate that PET use in initial staging and diagnosis can impact the expected prognosis of patients with HD. In a meta-analysis of twenty studies that looked at the diagnostic performance of PET in staging lymphoma, PET was found to have a median sensitivity of 90.3% and a median specificity of 91.1%.…”
Section: Lymphomamentioning
confidence: 92%